Culturally grounded strategies for suicide and alcohol risk prevention delivered by rural Alaska Native communities: A dynamic wait‐listed design evaluation of the Qungasvik intervention. Issue 1 (10th October 2022) - Allen, James; Charles, Billy; Fok, Carlotta Ching Ting; Lee, KyungSook; Grogan‐Kaylor, Andrew; ,; Rasmus, Stacy
Abstract: We examined the effectiveness of the Qungasvik (Tools for Life) intervention in enhancing protective factors as a universal suicide and alcohol prevention strategy for young people ages 12−18 living in highly affected rural Alaska Native communities. Four communities were assigned to immediate intervention or to a dynamic wait list. Outcomes were analyzed for 239 young people at four time points over two years of community intervention. Outcomes assessed two ultimate variable protective factors buffering suicide and alcohol risk, and three intermediate variable protective factors at the individual, family, and community level. Dose dependent intervention effects were associated with growth in ultimate but not intermediate variables. This evaluation of the Qungasvik intervention provides support for the effectiveness of its Indigenous strategies for suicide and alcohol misuse prevention in this rural Alaska Native setting. Though findings did not provide support for a theory of change where growth in ultimate variables is occasioned through effects on intermediate variables, research designs focused on young people who enter intervention at lower levels of preexisting protection hold promise for better understanding of intervention change processes. The Qungasvik intervention is responsive to an acute public health need for effective rural Alaska Native suicide and alcohol risk prevention strategies. Highlights: The Qungasvik intervention promotes protective factors to prevent suicide and alcohol misuse. We examined the effectiveness of Qungasvik in a dynamic wait‐listed community‐level trial. Intervention was associated with growth in ultimate variables protective from suicide and alcohol. This provides an evidence base for a rural Alaska Native suicide and alcohol prevention strategy. Findings support an Indigenous intervention strategy using a protective factor framework.